1990
DOI: 10.2307/1242342
|View full text |Cite
|
Sign up to set email alerts
|

Informational Efficiency of Markets for Stumpage

Abstract: This paper examines the weak-form informational efficiency of markets for pine sawtimber stumpage in the U.S. South. Analyses of annual and quarterly rates of price change generally indicate that stumpage markets are efficient. When viewed over monthly intervals, stumpage markets do not pass the tests for weak-form efficiency. This failure is attributed to friction in the market due to the time and cost involved in consumating timber sales. The results have implications for price-responsive timber harvest sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…Following [3]- [8], [12], I assume that the stumpage prices ( t P ) are exogenous and follow an autoregressive process AR(q) that is stationary 3 . I will discuss the case of a random walk process follow.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Following [3]- [8], [12], I assume that the stumpage prices ( t P ) are exogenous and follow an autoregressive process AR(q) that is stationary 3 . I will discuss the case of a random walk process follow.…”
Section: The Modelmentioning
confidence: 99%
“…Denoted by * * t t R P δ = − , the optimal reservation price where the optimal cut-off cost * δ satisfies Equation (12). Equation (12) deserves some comments.…”
Section: The Optimal Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Unit root tests are the main tools for defining market efficiency. Washburn and Binkley (1990) used a unit root test for the timber market of the south-eastern United States and used monthly, quarterly and annual data. They found that the timber mar-ket was efficient (non-stationary).…”
Section: Introductionmentioning
confidence: 99%
“…So the assumption of time series behaviour for the same time-span depends on the time interval of the data. Hultkrantz (1993) found that the pooled quarterly data are stationary and the market of timber stumpage price in the south-eastern United States is inefficient when he applied the DickeyFuller test to Washburn and Binkley's (1990) quarterly and annual data. Hultkrantz (1995) to 1996 as well as expert judgment, and due to their low number of observations modelled data as AR (1) process.…”
Section: Introductionmentioning
confidence: 99%